Nano-grooves etching on top of GaN-LED for light extraction enhancement. (June 2021) - Liu, Qifa; Wang, Zhenhai; Zhu, Lihui; Cheng, Xiefeng; Wang, Jin
Highlights: Etched through p-GaN layer nano-grooves to enhance light extraction for GaN-LED. The extraction efficiency increased by 50% in the ±10° incident angle. Extraction enhancement was realized by utilizing 0-order transmission diffraction. The simulation, fabrication result, theoretical explaining are all well matched. Abstract: Nano-grooves etched through top p-GaN layer were proposed to promote GaN-LED light extraction of small angles. The properties of grating with an optimized period of 500 nm were investigated theoretically and experimentally. The extraction efficiency increased by 50% in the ±10° incident angle range was verified by finite element modeling and rigorous coupled-wave analysis simulations, and sufficiently explained by transmission diffractive grating theory. The GaN-LED with a depth and period of 120 nm and 500 nm, respectively, etched inside a 20 µm diameter ring contact was fabricated and characterized by atomic force microscopy and electroluminescence testing, and the obtained results were in agreement with the design and simulations.